Use of an objective structured clinical exam (OSCE) for early identification of communication skills deficits in interns. (2nd January 2018) - Goldhamer, Mary Ellen J.; Cohen, Amy; Brooks, Michelle; Macklin, Eric A.; Co, John Patrick T.; Weinstein, Debra
Abstract: Introduction: There is limited information about whether OSCE during GME orientation can identify trainee communication deficits before these become evident via clinical performance evaluations. Methods: Ninety-seven interns matriculating to eight residency programs in six specialties at four hospitals participated in a nine-station communication skills OSCE. Ratings were based on the "Kalamazoo, adapted" communication skills checklist. Possible association with intern performance evaluations was assessed by repeated-measures logistic regression and ROC curves were generated. Results: The mean OSCE score was 4.08 ± 0.27 with a range of 3.3–4.6. Baseline OSCE scores were associated with subsequent communication concerns recorded by faculty, based on 1591 evaluations. A 0.1-unit decrease in the OSCE communication score was associated with an 18% higher odds of being identified with a communication concern by faculty evaluation (odds ratio 1.18, 95% CI 1.01–1.36, p  = 0.034). ROC curves did not demonstrate a "cut-off" score (AUC= 0.558). Non-faculty evaluators were 3–5 times more likely than faculty evaluators to identify communication deficits, based on 1900 evaluations. Conclusions: Lower OSCE performance was associated with faculty communication concerns on performance evaluations; however, a "cut-off" score was not demonstrated that could identify trainees for potential early intervention. Multi-source evaluation also identified trainees with communication skills deficits.